(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Systematic analysis of basement structures and Neogene morphotectonic elements -calibrated with research data on shear zones -has led to the construction of a new synthetic structural model for the Calabrian Arc. Six fault systems can be distinguished which have generated various types of basins, such as piggy-back,pull-apart and complex oblique strike-slip basins. These systems are determined by three morphotectonic patterns: A) N130 trending segments separated by oblique transversal thrust zones. B) SW-NE trending thrust zones representing the most internal part of the Calabrian accretionary wedge system. C) Radial wedge-shaped segments confining the collapsed Southern Tyrrhenian Basin with accompanying concentric patterns of tensional faults internally and dome-shaped uplift centres situated externally, determining the actual arc. The pactterns A and B can be linked to the Serravallian-Early Pliocene development of crustal shear zones ("Strike-Slip Cycle") while pattern C can be linked to the Pleistocene development (extreme vertical tectonics). The Late Pliocene was characterised by a tensional regime. A scenario for the Neogene Central Mediterranean geodynamics has been developed by means of three mechanisms: 1) NE-SW compression (dextral shear along the N. African margin); 2) diapiric rise within the Tyrrhenian area and 3) roll-back and detachment of remnants of the subducted Ionian lithosphere ("passive subduction"). The interplay of these three mechanisms led to basal detachment and the gravitational displacement of che Calabrian Element to the SE, superimposed upon oblique overthrusting in the Apennines. A proto-Mediterranean shear zone pattern -evolved as a result of sinistral megatorsion of the northern hemisphere -controlled the development of the Central Medicerranean. -